2009
DOI: 10.1182/blood-2008-07-169268
|View full text |Cite
|
Sign up to set email alerts
|

Impaired activation of platelets lacking protein kinase C-θ isoform

Abstract: Protein kinase C (PKC) isoforms have been implicated in several platelet functional responses, but the contribution of individual isoforms has not been thoroughly evaluated. Novel PKC isoform PKC-is activated by glycoprotein VI (GPVI) and protease-activated receptor (PAR) agonists, but not by adenosine diphosphate. In human platelets, PKC--selective antagonistic (RACK; receptor for activated C kinase) peptide significantly inhibited GPVI and PARinduced aggregation, dense and ␣-granule secretion at low agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 48 publications
(76 reference statements)
4
81
3
Order By: Relevance
“…PKCθ, the downstream of integrin α IIb β 3 , plays a crucial role in platelet α-granule exocytosis [37,38]. Research showed that PKCθ inhibited by PKC-θ RACK peptide significantly impaired platelet secretion [42]. In this study, we found that the expression of integrin α IIb β 3 in LPS-stimulated platelets was significantly increased.…”
Section: Figure 5: Effects Of Corm-2 On Platelet Munc18a Expression Asupporting
confidence: 60%
“…PKCθ, the downstream of integrin α IIb β 3 , plays a crucial role in platelet α-granule exocytosis [37,38]. Research showed that PKCθ inhibited by PKC-θ RACK peptide significantly impaired platelet secretion [42]. In this study, we found that the expression of integrin α IIb β 3 in LPS-stimulated platelets was significantly increased.…”
Section: Figure 5: Effects Of Corm-2 On Platelet Munc18a Expression Asupporting
confidence: 60%
“…A recent study by Nagy et al showed that activation of both GPVI and PAR induced phosphorylation on PKC- [24]. Marjoram et al also recently demonstrated a PLC dependent enhanced adhesion to a collagen related peptide by PAR peptides [23].…”
Section: Discussionmentioning
confidence: 98%
“…G q -mediated PLC␤ activation results in generation of inositol 1,4,5-trisphosphate and diacylglycerol, which promotes mobilization of intracellular calcium and activation of PKC, respectively (44). PKC is known to play a key role in G q -dependent platelet secretion and aggregation (34,36,45,46). PKC-dependent platelet activation requires its effector pleckstrin (47).…”
Section: Discussionmentioning
confidence: 99%